THE EFFECTIVENESS OF STEM CELL THERAPY IN MYOCARDIAL INFARCTION REVIEWED FROM UREUM, CREATININE AND KIDNEY HISTOPATHOLOGY LEVELS - Rahmi, Nur; Gunanti, Gunanti; Noviana, Deni; Harlina, Eva (Universitas Syiah Kuala, 2024)
This study aims to study the effectiveness of single placental stem cell therapy or cardiomyocyte combination in pigs experiencing myocardial infarction in terms of urea, creatinine and kidney organ histopathology values. A total of 9 pigs were divided int o three groups: without therapy (K1), single placental stem cell therapy (K2), and cardiomyocyte coculture combination therapy (K3). All pigs underwent circumflex artery ligation of the proximal coronary artery branch to stimulate cardiac ischemia and therapy was given after myocardial infarction and ST-elevation were formed. The pigs were then treated for eight weeks, euthanized and necropsied for kidney organ removal. The re sults showed a significant decrease in urea and creatinine values (P0.05) in K2 and K3 as compared to K1. Histopathology results showed a decrease in glomerular atrophy values (K2: 10.260.93 and K3: 12.441.21), tubular necrosis (K2: 13.673.76 and K3: 17.230.55), and tubular dilation (K2: 16.361.26 and K3: 18.031.76) and these values were significantly different than those observed in K1. It was concluded that the administration of placental stem cell therapy or combined with cardiomyocyte coculture could reduce urea, creatinine values, and improve kidney tissue histopathologically.